EKONOMICZNE I PRAWNE PODŁOŻE ZAWIERANIA KONTRAKTÓW KUPNA RZECZY PRZYSZŁEJ ORAZ KUPNA NADZIEI W STAROŻYTNYM RZYMIE - Chytła, Karolina (Zeszyty Prawnicze, 2017)
Economic and Legal Background of Signing Contracts of the Purchase of the Future Object and Hope in the Ancient Rome Summary The author analyzes economic background of entering into a contract of purchase of a future object (emptio rei speratae) and hope (emptio spei) in ancient Rome as well as legal regulations in this area. Amongst the most important economic reasons for creating particular types of bargain - selling contracts the author indicates territorial expansion of the early Empire, establishing the ordo equester, which allowed to generate the most important branches of economy, and eventually of the regular coining, which had a great impact on the trade development. The analysis of the legal solutions of the Roman law in this respect is made by comparing emptio rei speratae and emptio spei. Their analysis is based on following criteria: the role of a condition in the contract, the definitione of price, the liability for compensation, market attitude of a purchaser and salesman, who decided on the choice of one of the contracts. The conclusion that comes out of the article can force to the statement that in Rome of 2nd century ВС economy was so well developed that it allowed to come into a contract with e.g. delayed time limit of payment or delivery that there are basis to regard Forum Romanum as sui generis exchange of ancient times.